Quality of life of lung cancer patients - Zub Valeriy; Tolstanov Oleksandr; Kotuza Andrii; Manzhalii Elina (Current Issues in Pharmacy and Medical Sciences, 2023)
Lung cancer is one of the most prevalent forms of cancer in patients in Ukraine. The objective of the study was to identify the main problems in the quality of life of patients with lung cancer in order to optimize medical care for this patient group. A survey of 411 patients of oncology institutions in nine regions of Ukraine was conducted in the period from November 2021 to February 2022. The sociological survey was performed using the EORTC QLQ-C30 and QLQ-LC29 questionnaires. As of the pre-war period, the quality of life of lung cancer patients in Ukraine amounted to 49.12 points on a 100-point scale. According to the QLQ-C30 symptom scale, the highest score among the complaints of Ukrainian patients is that of financial difficulties, the second place is occupied by fatigue. According to the QLQ-LC29 symptom scale, patients with lung cancer were most concerned with “Fear of progression”. Ukrainian patients were least concerned about diarrhea and hemoptysis. When providing medical care to cancer patients, components to ensure the proper quality of their lives and psychosocial care, including the standardization of psychological care and its introduction in all institutions that provide medical care to cancer patients; organization of social and psychological support for cancer patients and their families; as well as educational work with relatives, colleagues, medical professionals on awareness of the need for social and psychological support for patients must be taken into account.